HIV/AIDS employees in Malaysia: are the laws and guidelines in Malaysia sufficient to protect employees with HIV/AIDS? / Ayusuffina Mohd Abdad and Nur Hanim Jamaludin - Mohd Abdad, Ayusuffina; Jamaludin, Nur Hanim (2008)
The topic of HIV/AIDS has been widely discussed, especially in a social context. However, the issue of HIV/AIDS in the workplace is still shrouded behind a veil of privacy and confidentiality. This is where our research comes in. Our research titled "HIV/AIDS employees in Malaysia: Are the laws and guidelines in Malaysia sufficient to protect employees with HIV/AIDS", will firstly look at the existing laws and guidelines in Malaysia to determine their sufficiency in protecting the rights of HIV//AIDS victims. From there, we will look at the policies in companies to see whether they conform to the existing laws and guidelines in protecting the rights of HIV/AIDS in relation to workplace discrimination. Lastly, to complete our research, we will find out whether there can be any recommendations and suggestions that could better protect the rights of HIV/AIDS victims, namely employees. After the completion of our research, we have determined that the existing laws are insufficient as we have no specific laws that govern the protection of HIV/AIDS victims, especially HIV/AIDS employees in the workplace as the current laws are all general in nature. The guidelines however, are sufficient but what they do lack is legal and binding authority. On the issue of policies in companies, we find that they do not conform to the guidelines in particular, as the issue of HIV/AIDS is not addressed in their policies. Hence, we have suggested that there should be a specific law on HIV/AIDS, especially in the protection of HIV/AIDS employees while the existing guidelines should automatically be part of the provisions of all polices in companies therefore making it binding on the whole workforce.